The thymus and T cell development: a primer - Holländer, Georg (Henry Stewart Talks, 2022)
The thymus, The thymus microenvironment, T cell development, Cortical thymic epithelial cell function, Medullary thymic epithelial cell function, T cell self-non-self-discrimination, Expression of tissue-restricted antigens, AIRE-deficiency